2011
DOI: 10.1007/s13592-011-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of selected Gram-negative non-fermenting bacteria isolated from honey bees (Apis mellifera carnica)

Abstract: -This study was conducted to improve the knowledge about bacteria associated with honey bees, Apis mellifera carnica. In this survey, the diversity of Gram-negative non-fermenting bacteria isolated and cultivated from pollen loads, honey sac, freshly stored nectar, and honey was investigated. Bacteria were characterized by a polyphasic approach. Based on morphological and physiological characteristics and comparison of isolates protein patterns after sodium dodecyl sulfate-polyacrylamide gel electrophoresis, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…In summary, the results of housekeeping gene sequence analysis corroborate the results from 16S rRNA gene sequence analyses, providing clear evidence that LMM 40 T and LMM 41 are only distantly related to hitherto-known species of the genus Porphyromonas ( and S1, available in IJSEM Online). ERIC PCR, carried out as described previously (Loncaric et al , 2011), also clearly distinguished the two isolates from the type strains of P. crevioricanis and P. asaccharolytica (Fig. S2).…”
supporting
confidence: 64%
“…In summary, the results of housekeeping gene sequence analysis corroborate the results from 16S rRNA gene sequence analyses, providing clear evidence that LMM 40 T and LMM 41 are only distantly related to hitherto-known species of the genus Porphyromonas ( and S1, available in IJSEM Online). ERIC PCR, carried out as described previously (Loncaric et al , 2011), also clearly distinguished the two isolates from the type strains of P. crevioricanis and P. asaccharolytica (Fig. S2).…”
supporting
confidence: 64%
“…However, in contrast to viral diagnostics, culturebased methods are still dominating in clinical microbiology (Mancini et al, 2010). Over the past years, sequence analysis of the 16S rRNA gene has allowed identification of several new bacterial species or bacterial communities (Woo et al, 2008;Loncaric et al, 2011) and represents the "gold standard" for bacteria classification because of quality and accuracy of a sequence-based method and the availability of comprehensive databases such as the Ribosomal Database Project (RDP) (Cole et al, 2014) (Euzéby, 1997;Parte, 2014). In general, public databases such as Basic Local Alignment Search Tool (BLAST) or the RDP yield better identification results for rare or highly pathogenic bacteria than quality-controlled databases such as RIDOM or MicroSeq 500 (Ruppitsch et al, 2007b).…”
Section: Identification Of Microorganismsmentioning
confidence: 99%
“…(Hu et al, 2012;Lewis et al, 2010).With the deepening of research, more and more pathogenic risk factors have been found, particularly, the continuous research on intestinal microflora find that the lecithin that people take from food may produce TMAO under the action of intestinal microorganisms, and such substance will promote the occurrence and development of atherosclerosis (AS), increasing the risk of cranial nerve injury (Kessler et al, 2006;Erşahin et al, 2010;Morais et al, 2013). Due to the vast territory of our country, the living environment and diet structure of the residents are very different, so there are great regional differences in the intestinal microflora (Geiger et al, 2011;Loncaric et al, 2011;Sereia et al, 2013;Seres et al, 2013), thus whether the intestinal microflora is an important triggering factor of large artery atherosclerosis (LAA) and transient ischemic attack (TIA) in China remains to be studied.…”
Section: Introductionmentioning
confidence: 99%